2019
DOI: 10.30651/jkm.v4i1.1852
|View full text |Cite
|
Sign up to set email alerts
|

Study Literature Peran Epidermal Growth Factor dalam Proses Penyembuhan Luka

Abstract: Background: Wounds occur when normal skin structures are damaged. Injury events in Indonesia have increased by 8.2% and the highest prevalence in South Sulawesi is 12.8%. One of the growth factors that play a role in the wound healing process is epidermal growth factor (EGF). EGF includes polypeptides that contain 53 amino acids, and EGF is present in all fluids in the body and platelets. This review aims to determine the role of EGF in the process of wound healing. Method: Data collected since 2017 using 8 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
2
0
2
Order By: Relevance
“…The bFGF is a growth factor secreted by fibroblasts for tissue repair, epithelial regeneration, and remodeling. (17) Previous studies have shown that human mesenchymal stromal cells (hMSCs) reduce FGF receptor 1 (FGFR1) expression, leading to unresponsiveness to bFGF, whereas fibroblasts maintain high FGFR1 expression. In hMSCs and fibroblasts, inhibition of actin-myosin interaction and MRTF/SRF activity decreases FGFR1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…The bFGF is a growth factor secreted by fibroblasts for tissue repair, epithelial regeneration, and remodeling. (17) Previous studies have shown that human mesenchymal stromal cells (hMSCs) reduce FGF receptor 1 (FGFR1) expression, leading to unresponsiveness to bFGF, whereas fibroblasts maintain high FGFR1 expression. In hMSCs and fibroblasts, inhibition of actin-myosin interaction and MRTF/SRF activity decreases FGFR1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Kondisi ini juga diungkapkan dalam temuan lain yang membahas dampak penandaan stoma site pada saat preoperatif dapat meningkatkan perawatan diri dan kualitas kesehatan pasien (Kim, Jang, dan Lee 2021). Berbagai pendekatan telah dilakukan untuk meningkatkan pengetahuan pasien diantaranya melalui media video (Salmawati, Yusuf, and Tahir 2019). Pendekatan edukasi berbasis video dilaporkan efektif pada kasus kaki diabetes (Hamzah, Yusuf, and Iswanti Afelya 2020).…”
Section: Pembahasanunclassified
“…Hasil penelitian lainnya menyebutkan bahwa pemberian edukasi menggunakan multimedia lebih signifikan meningkatkan pengetahuan dan keterampilan ostomate dibandingkan dengan edukasi konvensional (Wang et al, 2021). Pemberian edukasi menggunakan video secara signifikan dapat meningkatkan pengetahuan dan kemampuan pasien tentang cara perawatan stoma (Salmawati et al, 2019). Penelitian pendukung lain mengenai edukasi ostomate menyebutkan bahwa penggunaan aplikasi seluler terbukti memberikan efek lebih baik terhadap kemampuan merawat stoma sendiri dan kepuasan terhadap edukasi yang diberikan dibandingkan dengan pasien yang diedukasi menggunakan booklet (Yiğitoğlu & Şendir, 2021).…”
Section: Penelitian Fase IIIunclassified